2002
DOI: 10.1097/00006123-200203000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation for Acute Hemispheric Stroke after Carotid Endarterectomy: Is There Any Value?

Abstract: In this series, approximately one-half of hemispheric strokes complicating CEA had an underlying correctable lesion (occlusion or stenosis), and these patients typically had delayed-onset strokes. Approximately one-half of these patients improved early as a result of reopening, although computed tomography revealed new infarcts in most of them. Urgent carotid repair may benefit a minority of selected patients who have a major stroke after CEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 12 publications
0
16
0
1
Order By: Relevance
“…14 The frequency of perioperative strokes in NASCET is in line with other reports that cite a 0.8% to 3.9% incidence. 4,[8][9][10]12,15 Perioperative strokes after CEAs are usually due to postoperative surgical site thrombosis and embolism. 16 Several studies have attempted to identify risk factors for these immediate strokes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The frequency of perioperative strokes in NASCET is in line with other reports that cite a 0.8% to 3.9% incidence. 4,[8][9][10]12,15 Perioperative strokes after CEAs are usually due to postoperative surgical site thrombosis and embolism. 16 Several studies have attempted to identify risk factors for these immediate strokes.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of acute post-CEA stroke, many centers have begun incorporating CT angiography before re-exploration. 4,10,12 This imaging modality can delineate not only whether the carotid is occluded but also whether there is a tandem intracranial occlusion from an embolus, for example, an M1 middle cerebral artery occlusion. This is important because an intracranial occlusion cannot be addressed with a surgical exploration.…”
mentioning
confidence: 99%
“…Acute thrombosis after CEA is the most common cause of perioperative stroke, accounting for up to 75% of cases 4. Distal intimal flap represents another important cause of such a complication 3…”
Section: Discussionmentioning
confidence: 99%
“…Other causes include carotid artery (CA) dissection, hypotension, embolization, and intracerebral hemorrhage 1. Controversy exists with regard to which diagnostic tests should be performed and which definitive therapy is optimal 4 5. We recently experienced a case in which stent-graft placement was used for treatment of a symptomatic occlusion of the CA that occurred immediately after CEA.…”
Section: Introductionmentioning
confidence: 99%
“…However, as acute thrombosis is rare, it is difficult to accumulate evidence for a preferred treatment strategy. Setacci et al reported positive results of embolectomy, with or without stent removal, in cases of acute stent thrombosis following stenting while surgical treatment was commonly used in cases of thrombosis after endarterctomy 9,15,16. We chose medical management rather than surgery, because the event occurred in the angiography suite allowing immediate drug infusion.…”
Section: Discussionmentioning
confidence: 99%